American society of transplantation and cellular therapy, center of international blood and marrow transplant research, and European society for blood and marrow transplantation clinical practice recommendations for transplantation and cellular therapies in mantle cell lymphoma - Munshi, Pashna N.; Hamadani, Mehdi; Kumar, Ambuj; Dreger, Peter; Friedberg, Jonathan W.; Dreyling, Martin; Kahl, Brad; Jerkeman, Mats; Kharfan-Dabaja, Mohamed A.; Locke, Frederick L.; Shadman, Mazyar; Hill, Brian T.; et al. (Transplantation and cellular therapy, 2021)
Autologous (auto-) and allogeneic (allo-) hematopoietic cell transplantation (HCT) are accepted treatment modalities in contemporary treatment algorithms for mantle cell lymphoma (MCL). Chimeric antigen receptor (CAR) T cell therapy recently received approval for MCL; however, its exact place and sequence in relation to HCT remain unclear. The American Society of Transplantation and Cellular Therapy, Center of International Blood and Marrow Transplant Research, and the European Society for Blood and Marrow Transplantation jointly convened an expert panel to formulate consensus recommendations for role, timing, and sequencing of auto-HCT, allo-HCT, and CAR T cell therapy for patients with newly diagnosed and relapsed/refractory (R/R) MCL. The RAND-modified Delphi method was used to generate consensus statements. Seventeen consensus statements were generated, with a few key statements as follows: in the first line setting, auto-HCT consolidation represents standard of care in eligible patients, whereas there is no clear role of allo-HCT or CAR T cell therapy outside of clinical trials. In the R/R setting, the preferential option is CAR T cell therapy, especially in patients with MCL failing or intolerant to at least one Bruton's tyrosine kinase inhibitor, while allo-HCT is recommended if CAR T cell therapy fails or is infeasible. Several recommendations were based on expert opinion, where the panel developed consensus statements for important real-world clinical scenarios to guide clinical practice. In the absence of contemporary evidence-based data, the panel found RAND-modified Delphi methodology effective in providing a formal framework for developing consensus recommendations for the timing and sequence of cellular therapies for MCL.
Gesehen am 11.11.2021